Penggunaan Media Kartu Kuartet Dalam Meningkatkan Kemampuan Menulis Teks Deskripsi - Indrayanti, Listy Dwi; Hamsa, Akmal; Sarkiah, Sarkiah (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the improvement of the ability to write description text of class VII students of SMP Negeri 27 Makassar. In this classroom action research, the data collected include teacher activity observation, description writing test and field notes. Qualitative and quantitative data analysis techniques were carried out in each learning cycle, so that the results of the analysis could be concluded to determine the action plan to be implemented in the next cycle. The results showed that the implementation of learning had improved. Students' learning outcomes in writing descriptions using quartet card media in cycle I were only 56.25% who reached the completion grade. In the next cycle, 84.37% of students reached the completion score. The obstacles that arose in learning in Cycle I included the teacher's voice was not loud enough, the teacher did not master the class, students fought over the quartet cards, and the explanation of the material delivered by the teacher was not clear. While in Cycle II no significant obstacles were found. For this reason, quartet card media is suitable for use in writing descriptions, because it is proven to improve learning.